Chemical and Antimicrobial Profiling of Propolis from Different Regions within Libya. - Weam Siheri; Tong Zhang; Godwin Unekwuojo Ebiloma; Marco Biddau; Nicola Woods; Muattaz Yassein Hussain; Carol J Clements; James Fearnley; RuAngelie Edrada Ebel; Timothy Paget; Sylke Muller; Katharine C Carter; et al. (PLoS ONE)
Extracts from twelve samples of propolis collected from different regions of Libya were tested for their activity against Trypanosoma brucei, Leishmania donovani, Plasmodium falciparum, Crithidia fasciculata and Mycobacterium marinum and the cytotoxicity of the extracts was tested against mammalian cells. All the extracts were active to some degree against all of the protozoa and the mycobacterium, exhibiting a range of EC50 values between 1.65 and 53.6 μg/ml. The toxicity against mammalian cell lines was only moderate; the most active extract against the protozoan species, P2, displayed an IC50 value of 53.2 μg/ml. The extracts were profiled by using liquid chromatography coupled to high resolution mass spectrometry. The data sets were extracted using m/z Mine and the accurate masses of the features extracted were searched against the Dictionary of Natural Products (DNP). A principal component analysis (PCA) model was constructed which, in combination with hierarchical cluster analysis (HCA), divided the samples into five groups. The outlying groups had different sets of dominant compounds in the extracts, which could be characterised by their elemental composition. Orthogonal partial least squares (OPLS) analysis was used to link the activity of each extract against the different micro-organisms to particular components in the extracts.